2020
DOI: 10.1017/s1751731119001708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ractopamine and conjugated linoleic acid on performance of late finishing pigs

Abstract: The dietary inclusion of feed additives to improve the carcass characteristics of the final product is of great importance for the pork production chain. The aim of our study was to evaluate the effects of the association of ractopamine (RAC) and conjugated linoleic acid (CLA) on the performance traits of finishing pigs during the last 26 days prior to slaughter. In total, 810 commercial hybrid barrows were used. Animals were distributed among treatments according to a randomised block design in a 3 × 3 factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Notably, when assessing the complete study period (81 d) in terms of productive behavior, no significant differences were found between the groups of pigs that received a diet supplemented with CrMet-S, CrMet-L, and RAC, suggesting an approximation of the effects of CrMet to those of RAC on productive behavior. However, improvement in the ADG and final BW of the pigs could be attributed to an increase in protein synthesis in the tissue of their skeletal muscle induced by organic Cr (CrMet) [ 11 , 15 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, when assessing the complete study period (81 d) in terms of productive behavior, no significant differences were found between the groups of pigs that received a diet supplemented with CrMet-S, CrMet-L, and RAC, suggesting an approximation of the effects of CrMet to those of RAC on productive behavior. However, improvement in the ADG and final BW of the pigs could be attributed to an increase in protein synthesis in the tissue of their skeletal muscle induced by organic Cr (CrMet) [ 11 , 15 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of this agonist is currently questionable owing to the global market trend, and it is banned in different countries due to its potential detrimental effects on human health [ 12 , 13 , 14 ]. Therefore, the pork industry is seeking a growth-promoting compound that can replace RAC [ 15 ].…”
Section: Introductionmentioning
confidence: 99%